Recent progress of personal glucose meters integrated methods in food safety hazards detection. Issue 27 (22nd September 2022) - Xing, Xiuguang; Yao, Li; Yan, Chao; Xu, Zhenlin; Xu, Jianguo; Liu, Guodong; Yao, Bangben; Chen, Wei
Abstract: Development of personal glucose meters (PGMs) for blood glucose monitoring and management by the diabetic patients has been a long history since its first invention in 1968 and commercial application in 1975. The main reasons for its wide acceptance and popularity can be attributed mainly to the easy operation, test-to-result model, low cost, and small volume of sample required for blood glucose concentration test. During past decades, advances in analytical techniques have repurposed the use of PGMs into a general point-of-care testing platform for a variety of non-glucose targets, especially the food hazards. In this review, we summarized the recent published research using PGMs to detect the food safety hazards of mycotoxins, illegal additives, pathogen bacteria, and pesticide and veterinary drug residues detection with PGMs. The progress on PGM-based detection achieved in food safety have been carefully compared and analyzed. Furthermore, the current bottlenecks and challenges for practical applications of PGM for hazards detection in food safety have also been proposed.